Hubungan Deprivasi Kolektif Dan Agresivitas - Rumandjo, Karolin Rista (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
This study aims to prove empirically the relationship of collective deprivation and aggressiveness. Variables that will be examined in this study is composed of the independent variable (X), namely collective deprivation and dependent variable (Y) is aggressiveness. The hypothesis in this study, is